Profile of women with lymphedema after breast cancer treatment - Thais de Oliveira Gozzo; Gabriela Aguado; Aniele Tomadon; Marislei Sanches Panobianco; Maria Antonieta Spinoso Prado
ABSTRACT Objective: To identify the profile of women with lymphedema after breast cancer treatment. Methods: This is a descriptive, retrospective and quantitative study with data from medical records of women with lymphedema who began treatment between 2010 and 2015 in a rehabilitation center. An instrument was used for data collection to characterize the participants and analysis was performed by means of descriptive statistics, the Chi-Square test and Fisher's exact test. Results: 235 women with a mean age of 56.8 years were included, with an association between lymphedema and age (p = 0.016). It was observed that 76.6% of the sample had some comorbidity associated with breast cancer, especially hypertension (48.1%). They underwent radical surgery (60%), axillary lymphadenectomy (77.9%), sentinel lymph node biopsy (16.6%) and radiotherapy (74%). Treatments carried out for lymphedema were decongestant therapy and complementary treatments with 95.7% of adherence of women to therapies. Conclusion and implications for practice: Women with lymphedema presented risk factors such as radical surgery, axillary lymphadenectomy and radiotherapy, and good adherence to the required treatments of lymphedema. Knowing the profile of this population is crucial to the treatment choice.